Purine–Hydrazone Scaffolds as Potential Dual EGFR/HER2 Inhibitors - Fatemah S. Albalawi; Mashooq A. Bhat; Ahmed H. Bakheit; A. F. M. Motiur Rahman; Nawaf A. Alsaif; Alan M. Jones; Isolda Romero-Canelon (Pharmaceuticals)
Background/Objectives: The dual targeting of epidermal growth factor receptor (EGFR) and human epidermal growth factor receptor 2 (HER2) represents an effective approach for cancer treatment. The current study involved the design, synthesis, and biological evaluation of a new series of purine-containing hydrazones, 6–24 (a,b), as anticancer agents targeting EGFR and HER2 kinases. Methods: The proposed compounds were initially screened in silico using molecular docking to investigate their binding affinity to the active sites of EGFR and HER2 kinase domains. Subsequently, the compounds were synthesized and evaluated in vitro for their antiproliferative activity, using the MTT assay, against the various cancer cell lines A549, SKOV-3, A2780, and SKBR-3, with lapatinib as the reference drug. The most active derivatives were then examined to determine their inhibitory activity against EGFR and HER2 kinases. Results: Among the assessed compounds, significant antiproliferative activity was demonstrated by 19a, 16b, and 22b. 19a exhibited substantial anticancer efficacy against A549 and SKBR-3, with IC50 values of 0.81 µM and 1.41 µM, respectively. This activity surpassed lapatinib, which has an IC50 of 11.57 µM on A549 and 8.54 µM on SKBR-3 cells. Furthermore, 19a, 16b, and 22b exhibited superior EGFR inhibitory efficacy compared with lapatinib (IC50 = 0.13 µM), with IC50 values of 0.08, 0.06, and 0.07 µM, respectively. Regarding HER2, 22b demonstrated the greatest potency with an IC50 of 0.03 µM, equipotent to lapatinib (IC50 = 0.03 µM). Flow cytometry analysis of A549 cells treated with 19a and 22b indicated their ability to arrest the cell cycle during the G1 phase and to trigger cellular apoptosis. Conclusions: Compounds 19a, 16b, and 22b represent intriguing candidates for the development of an anticancer agent targeting EGFR and HER2 kinases.